The Relationship Between Caffeinated Beverages And The Risk Of Osteoporosis In The Elderly Posyandu Surakarta - Siti Anisa; Dea Linia Romadhoni; Alinda Nur Ramadhani; Dita Mirawati (STIKES Telogorejo Semarang, 2024)
Background: The prevalence of osteoporosis in elderly Indonesian women in the age of 50-70 years and above 70 years is 23% and 53%. Osteoporosis is a disorder of bone metabolism due to a loss of bone mass. The decrease in bone mass is caused by the speed of bone resorption which is greater than the speed of bone formation gradually, the bones become brittle and easily broken, even by light pressure. Purpose: determine the relationship between caffeinated drinks and the risk of Osteoporosis. Methods: Qualitative research with a cross-sectional design, which is research that intends to understand the phenomenon of what the research subject experiences with the observation method. Result: the results of this study indicate a significant relationship between caffeinated drinks and the risk of osteoporosis with a value of (p=0.007). Conclusion: As a result, there is a strong connection caffeinated drinks and the risk of osteoporosis in the elderly in Posyandu Surakarta